The effect of melatonin in rats with uterine torsion on uterus contractions, and the levels of ADMA, SDMA, arginine, Hsp90, TLR4, and NF-?B - Dogan, Halef; Risvanli, Ali; Saat, Nevzat; Gul, Huseyin Fatih; Ilhan, Necip; Seker, Ibrahim; Sahna, Engin (Ankara Univ Press, 2019)
In this study was aimed at reducing uterine damage and increasing fertility after uterine torsion in pregnant animals. With this aim, uterine torsion was experimentally formed in 35 rats that were between 18-19 days pregnant. The animals were randomly divided into five groups, and melatonin was administered prior to torsion, at the time of torsion, and detorsion (10 mg/kg/gun IP). Ovario-hysterectomy operation was performed on all animals on the first day following parturition. Subsequently, from the obtained uterus samples, determination of the levels of asymmetrical dimethyl arginin (ADMA), symmetrical dimethyl arginin (SDMA), and arginine was made using the high-performance liquid chromatography (HPLC) and levels of Heat shock protein 90 (Hsp90), TLR4 (Toll Like Receptor 4) and NF kappa B (Nuclear factor kappa-light-chain-enhancer of activated B cells) were measured using the Western blot technique. The contraction-relaxation responses of the myometrium were also determined in the organ baths. According to the results of the western blot, higher protein expressions than those of the control group were determined in the second, third, fourth, and fifth groups in Hsp90, TLR4, NF-kappa B. The lowest values of arginine and ADMA were found in Group 3, whilst the lowest SDMA value was determined in Group 1. It was determined that melatonin reduces tissue damage secondary to torsio uteri and, furthermore, that administration of this hormone at the time of torsion formation was more effective than its administration at the time of detorsion.
Torsiyo uterili ratlarda melatoninin uterus kontraksiyonları, ADMA, SDMA, arjinin, Hsp90, TLR4 ve NF?B düzeylerine etkisi
Keywords: Melatonin; pregnancy; rats; torsion; uterine